Системний аналіз: еволюція і перспективи подальшого розвитку - Korshevniuk, Lev O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2020)
The paper considers the historical formation and directions of further developing system ideas in science, problem changes, and the evolution of a system analysis methodology. There are six historical periods defined from the first ancient "embryonic" (III century BC – beginning of AD) to the sixth modern "rising" period (beginning of the XX century – 2020s). Each period is described in the parameters of time intervals, main territories, outstanding scientists and researchers, events, objects of scientific studies, issues, and methodology. The seventh future "integration" period (the 2020s–2050s) is predicted to be characterized by informal, dynamic trans-industry problems in complex systems of various nature and will require real-time solutions. The issue discovers that technical science development's key and perspective direction is the methodological integration of system analysis procedures and artificial intelligence technologies.